(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
The aim of the investigation was to develop and evaluate thermoreversible in situ nasal gel formulations of repaglinide (REP) and to establish correlation between its in vitro release and ex vivo permeation profiles. The solubility of REP was enhanced by preparing solid dispersions (SDs) with hydrophilic carriers (PVP K30/ PEG 6000/ poloxamer 188) in different weight ratios. REP: PVP K30 (1:5) was selected as the optimized SD as it showed highest enhancement in solubility (405%). The optimized SD was characterized by SEM and DSC and incorporated into a blend of thermoreversible and mucoadhesive polymers (poloxamer 407 and carbopol 934 P) by cold technique to form in situ gels (F1-F6). The prepared in-situ gels were evaluated for various pharmacotechnical features and the formulation F3 exhibited least gelling time of 6.1± 0.20, good mucoadhesive property to ensure sufficient residence time at the site of application and a %CDR of 82.25%. The ex vivo permeation characteristics across goat mucosa can be summarized as CDP of 78.7%, flux = 6.80 mg/cm2/h; permeability coefficient of 2.02 mg/h and zero order kinetics. On correlating the CDR profile of F3 with that of its CDP profile, a R2 value of 0.991 (slope= 0.921) was observed. The value of slope approximating one, suggested that almost entire amount of drug released from F3 was capable of permeating across the nasal mucosa, ex-vivo indicating that in-situ nasal gels of REP for systemic action can be successfully developed for the management non-insulin dependent type-II diabetes mellitus.